"The Limits of my Language are the Limits of my World." The effects of language learning disorders on foreign language learning and the possible solutions - Ágústína Gunnarsdóttir 1983- (2014)
There are a number of learning disorders that affect language acquisition in the native language but chief among them are dyslexia and specific language impairment (SLI). Their effects are found in the first language and extend to any subsequent languages, including foreign languages. As curriculum guidelines in Iceland feature the mandatory learning of a number of foreign languages and the Icelandic institutions of higher learning use foreign languages quite heavily in their instruction, proficiency in foreign languages in Iceland becomes paramount. Yet students with the dyslexia or SLI do not seem to receive any remedial teaching during the important secondary school years. The thesis seeks to describe what types of language learning challenges these students face, and what can be done to assist them in their education. To that end the thesis features an extensive literature review and a small study that employs interviews to gather information. Three interviews were conducted, two with dyslexic students attending secondary school and one with an English teacher teaching in secondary school. The main conclusions from the study showed that Icelandic students with language learning disorders frequently struggle in their language learning process and that the assistance that they are provided with is limited to external aids such as audio books and extended exam times. Teachers seem willing to assist these students but must usually forego this because of time constraints. The findings of the study are supported by previous studies. The thesis also showcases the various teaching methods and alteration to teaching methods that could better suit students with language learning disorders. However, in the current climate a concerted effort from school officials and teachers, as well as support from the government, is needed to implement these modifications.